Assessment of increased energy efficiency of vehicles with a rational reduction of engine capacity - Podrigalo, Mikhail; Tarasov, Yurii; Kholodov, Mykhailo; Shein, Vitaly; Tkachenko, Olexander; Kasianenko, Oleksii; Подригало, Михайло Абович; Тарасов, Юрій Володимирович; Холодов, Михайло Павлович; Шеїн, Віталій Сергійович; Ткаченко, Олександр Сергійович; Касьяненко, Олексій Віталійович (Харківський національний автомобільно-дорожній університет, 2022)
Problem. The tendency to reduce Engine displacement, which has emerged in recent years in the global automotive industry, is due to the need to improve the environmental situation and energy efficiency of vehicles. Goal. The aim of the study is to increase the energy efficiency of vehicles by rationally reducing the maximum effective engine capacity. Methodology. In the paper authors used the method of partial accelerations implemented in a mobile registration and measurement complex, which allowed authors to obtain an improved formula for calculating aerodynamic drug. Experimental studies of car aerodynamics were also conducted. Results. In the study presents the results of the authors' research, which made it possible to prove the possibility of reducing the e internal combustion engine capacity while maintaining the specified maximum speed and the specified level of indicators of the car dynamic properties. Originality. The relationship between the use of maximum engine capacity and the relative change in the effective specific fuel consumption of a carburetor gasoline engine, with direct injection of gasoline and diesel were determined. Practical value. Calculations performed on the example of the ZAZ-1103 "Slavuta" car showed that a rational reduction in effective engine capacity allows to reduce fuel consumption by 9.5% for carburetor gasoline engine, and for an engine with direct injection of gasoline by 6.7 % and for diesel engines, by 20.3%.
Оцінка підвищення енергоефективності автомобілів при раціональному зниженні потужності двигунів
Keywords: energy efficiency; vehicle; internal combustion engine; aerodynamic drag; fuel consumption; енергоефективність; автомобіль; двигун внутрішнього згоряння; аеродинамічний опір; витрата палива; 629.331.064; 10.30977/AT.2219-8342.2022.51.0.03